The association between multiple intestinal helminth infections and blood group, anaemia and nutritional status in human populations from Dore Bafeno, southern Ethiopia. Issue 2 (June 2014) - Degarege, A.; Animut, A.; Medhin, G.; Legesse, M.; Erko, B.
Abstract In this cross-sectional study, the associations between helminth infections and ABO blood group, anaemia and undernutrition were investigated in 480 febrile outpatients who visited Dore Bafeno Health Centre, southern Ethiopia, in December 2010. Stool specimens were processed using the Kato–Katz method and examined for intestinal helminth infections. Haemoglobin level was measured using a HemoCue machine and blood group was determined using an antisera haemagglutination test. Nutritional status of the study participants was assessed using height and weight measurements. Among the study participants, 50.2% were infected with intestinal helminths. Ascaris lumbricoides (32.7%), Trichuris trichiura (12.7%), Schistosoma mansoni (11.9%) and hookworm (11.0%) were the most frequently diagnosed helminths. The odds of infection and mean eggs per gram of different intestinal helminth species were comparable between the various blood groups. Among individuals who were infected with intestinal helminth(s), the mean haemoglobin level was significantly lower in individuals harbouring three or more helminth species and blood type AB compared to cases with double or single helminth infection and blood type O, respectively. The odds of being underweight was significantly higher in A. lumbricoides and T. trichiura infected individuals of age ≤ 5 and ≥ 20 years, respectively, when compared to individuals of the matching age group without intestinal helminths. In conclusion, infection with multiple intestinal helminths was associated with lower haemoglobin level, which was more severe in individuals with blood type AB. Future studies should focus on mechanisms by which blood group AB exacerbates the helminth-related reduction in mean haemoglobin level.